1994
DOI: 10.1016/0735-1097(94)90879-6
|View full text |Cite
|
Sign up to set email alerts
|

Distinct gap junction protein phenotypes in cardiac tissues with disparate conduction properties

Abstract: Although most cardiac gap junctions contain connexin40, connexin43 and connexin45, the relative amounts of each of these connexins vary considerably in cardiac tissues with different conduction properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(108 citation statements)
references
References 35 publications
3
102
0
3
Order By: Relevance
“…It is of interest that studies of heart showed remarkable similarities to observations in brain (Davis et al, 1994;GarciaDorado et al, 2004). Bystander death is prominent in ischemic heart and was first observed in the myocardium (Garcia-Dorado et al, 1989;Ruiz-Meana et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that studies of heart showed remarkable similarities to observations in brain (Davis et al, 1994;GarciaDorado et al, 2004). Bystander death is prominent in ischemic heart and was first observed in the myocardium (Garcia-Dorado et al, 1989;Ruiz-Meana et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…[5,6]. Cx45 is detected in sinoatrial and atrioventricular nodes, atrioventricular bundle and branches [7,8]. …”
mentioning
confidence: 99%
“…Three different connexins have been identified in cardiac myocytes: Cx43, connexin45 (Cx45), and connexin40 (Cx40). 8 These cardiac connexins are expressed in different amounts and combinations in different regions of the heart. For example, ventricular myocytes express Cx43 and Cx45, whereas atrial myocytes express Cx43, Cx45, and Cx40.…”
Section: Intercellular Coupling At Gap Junctionsmentioning
confidence: 99%